Neuroimaging markers of clinical progression in chronic inflammatory demyelinating polyradiculoneuropathy - Pitarokoili, Kalliopi (Ther Adv Neurol Disord, 2019)
BACKGROUND: One of the main goals of novel, noninvasive imaging techniques like high-resolution nerve ultrasound (HRUS) and corneal confocal microscopy (CCM) is the prediction of treatment response for patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). METHODS: A total of 17 patients with CIDP were examined prospectively at baseline and every 9 months over a period of 18 months using CCM to quantify corneal nerve degeneration markers and immune cell infiltration as well as HRUS to detect changes of the cross-sectional area (CSA) of the peripheral nerves. Additionally, skin biopsy of the distal and proximal leg as well as quantitative sensory testing were performed at the first follow-up visit. RESULTS: A value of more than 30 total corneal cells/mm(2) in CCM at baseline identified patients with clinical progression with a sensitivity/specificity of 100% in our cohort. Corneal nerve fiber density and length remained low and stable over the study period and intra-epidermal fiber density was markedly reduced in the majority of the patients. Furthermore, an increase in Bochum ultrasound score (BUS), which summarizes the CSA of the ulnar nerve in Guyons’ canal, the ulnar nerve in the upper arm, the radial nerve in the spiral groove and the sural nerve between the gastrocnemius muscle, and a maximum BUS of 4 at study initiation identified patients with disease progression (sensitivity 80%, specificity 88%). CONCLUSIONS: BUS and corneal total cell infiltration seem to represent early markers for clinical progression in CIDP, thus having the potential to identify at-risk patients and impact treatment decisions.